Advances in systems, computing sciences and software engineering Proceedings of SCSS 2005 - Sobh, Tarek (Springer Netherlands, 2006)
Advances in Systems, Computing Sciences and Software Engineering This book includes the proceedings of the International Conference on Systems, Computing Sciences and Software Engineering (SCSS’05). The proceedings are a set of rigorously reviewed world-class manuscripts addressing and detailing state-of-the-art research projects in the areas of computer science, software engineering, computer engineering, systems sciences and engineering, information technology, parallel and distributed computing and web-based programming. SCSS’05 was part of the International Joint Conferences on Computer, Information, and Systems Sciences, and Engineering (CISSE’05) (www. cisse2005. org), the World’s first Engineering/Computing and Systems Research E-Conference. CISSE’05 was the first high-caliber Research Conference in the world to be completely conducted online in real-time via the internet. CISSE’05 received 255 research paper submissions and the final program included 140 accepted papers, from more than 45 countries. The concept and format of CISSE’05 were very exciting and ground-breaking. The PowerPoint presentations, final paper manuscripts and time schedule for live presentations over the web had been available for 3 weeks prior to the start of the conference for all registrants, so they could choose the presentations they want to attend and think about questions that they might want to ask. The live audio presentations were also recorded and were part of the permanent CISSE archive, which also included all power point presentations and papers. SCSS’05 provided a virtual forum for presentation and discussion of the state-of the-art research on Systems, Computing Sciences and Software Engineering.